Is a higher estimated dose of radiation to immune cells predictive of survival in patients with locally advanced non-small cell lung cancer treated with thoracic radiotherapy?. (June 2021) - Yin, Xiaoming; Luo, Jing; Xu, Cai; Meng, Chunliu; Zhang, Jiaqi; Yu, Hao; Liu, Ningbo; Yuan, Zhiyong; Wang, Ping; Sun, Yunchuan; Zhao, Lujun
Highlights: EDRIC was an independent prognostic factor for metastasis of patients with LA-NSCLC who received thoracic radiotherapy. EDRIC was affected by gross tumor volume (GTV) and lymph node (N) stage. The association between EDRIC and overall survival (OS) was influenced by GTV. EDRIC showed a trend of negative correlation with OS in patients with smaller GTV. Abstract: Background and purpose: In previous studies, the estimated dose of radiation to immune cells (EDRIC) showed a correlation with overall survival (OS) of patients with locally advanced non-small cell lung cancer (LA-NSCLC) who received thoracic radiotherapy. However, several factors such as gross tumor volume (GTV) and lymph node (N) stage may impact EDRIC. The purpose of this study was to identify the factors influencing EDRIC and to further assess the prognostic relevance of EDRIC. Materials and methods: We retrospectively analyzed 201 patients with LA-NSCLC who received radiotherapy between 2012 and 2017. EDRIC was calculated based on the model developed by Jin et al. Kaplan–Meier method and Cox proportional hazards regression were used to analyze the correlation of potential factors with OS, local progression-free survival (LPFS), and distant metastasis-free survival (DMFS). Spearman's rank correlation was used to assess the correlation between variables. Results: Both GTV and N stage showed a positive correlation with EDRIC ( r = 0.347, P < 0.001 and r = 0.249, P < 0.001, respectively). EDRIC was independently associated with DMFS (HR 1.185, P < 0.001). GTV was associated with OS (HR 1.006, P < 0.001), LPFS (HR 1.003, P = 0.017), and DMFS (HR 1.003, P = 0.032). While using GTV as a stratification factor in Kaplan–Meier analysis, EDRIC showed a trend of negative correlation with OS in GTV ≤ 66.6 cm 3 group ( P = 0.061). Conclusion: EDRIC was an independent prognostic factor for metastasis and it was affected by GTV and N stage. However, the effect of EDRIC on OS was influenced by GTV.